Longitudinal Association of Carotid Plaque Presence and Intima-Media Thickness With Depressive Symptoms in the Elderly. Issue 5 (May 2015) - Prugger, Christof; Godin, Ophelia; Perier, Marie-Cécile; Ritchie, Karen; Helmer, Catherine; Empana, Jean-Philippe; Tzourio, Christophe; Dufouil, Carole
<x xml:space="preserve">Abstract</x> Objective— To investigate prospectively whether subclinical vascular disease is associated with future depressive symptoms in the elderly. Approach and Results— A multicenter cohort of community-dwelling individuals aged 65 to 85 years was examined for carotid plaque presence and common carotid artery intima-media thickness at baseline and followed up after 2, 4, 7, and 10 years. At baseline and follow-up examinations, depressive symptoms were assessed using the Center for Epidemiologic Studies Depression Scale (CES-D). High level of depressive symptoms was defined as a CES-D score >16 in men and >22 in women. Among 4125 participants (58% women) at baseline, men more frequently showed carotid plaque presence and had higher mean common carotid artery intima-media thickness than women. After adjustment for major cardiovascular risk factors, carotid plaque presence was associated with a higher CES-D score at the 10-year follow-up in men (+1.46; 95% confidence interval, 0.71–2.20; P<0.001), but not in women. When restricting analyses to individuals without cardiovascular disease at baseline, carotid plaque presence increased the likelihood of high level of depressive symptoms at follow-up examinations in men (odds ratio, 1.47; 95% confidence interval, 1.06–2.05; P=0.022), but not in women. One SD increase in log-transformed common carotid artery intima-media thickness was associated with a higher CES-D score at the 10-year follow-up in women (+0.55; 95% confidence interval, 0.16–0.95; P=0.006) and men (+0.40; 95% confidence interval, 0.02–0.78; P=0.037). Common carotid artery intima-media thickness did not increase the likelihood of high level of depressive symptoms at follow-up in both sexes. Conclusions— Subclinical vascular disease is associated with the progression of depressive symptoms in elderly men and women and the occurrence of high level of depressive symptoms in elderly men.